Nutritional requirements and precise fertilization of wine grapes in the eastern foothills of Helan Mountain - Jiang, Tingting; Yan, Pengke; Ma, Tinghui; Wang, Rui (International Journal of Agricultural and Biological Engineering, 2022)
Cabernet Sauvignon grapes in the wine-producing area of Helan Mountain, East Ningxia, China, were the research object in this study. The dissection of the roots and branching stems method was used to explore the dynamic changes in the nitrogen, phosphorus, and potassium nutrient requirements of wine grapes over a number of growth stages. The results showed that over the whole growth period, the nitrogen content of the roots was the highest during the leaf-expansion stage and lowest during the turning-color stage, and that the nitrogen content of the leaves and fruit showed a downward trend as growth progressed. The nitrogen content of the secondary branches was lowest during the fruit expansion stage and highest during the leaf-expansion stage; and the phosphorus content of the roots was the highest during the leaf-expansion stage and lowest during the fruit expansion stage. The phosphorus content of the trunk and primary branches showed a trend of “rising-falling-rising”. The phosphorus content of the leaves and secondary branches were lowest during the turning-color stage, whereas the phosphorus content of the fruit was at its highest during this stage. The potassium contents of the secondary branches and fruit showed a downward trend, but the potassium content of the leaves was highest during the fruit expansion stage and lowest in the nutrient return stage. Over the whole growth period, the accumulation of nitrogen, phosphorus, and potassium in wine grapes was 129.92 kg/hm2, 41.51 kg/hm2, and 189.47 kg/hm2, respectively, the total requirements for N, P2O5, and K2O were 262.38 kg/hm2, 288.15 kg/hm2, and 569.04 kg/hm2, respectively, and the reasonable nutrient requirement ratio was 1.00:1.10:2.17. Keywords: wine grapes, macronutrients, nutritional diagnosis, fertilizer requirements, the eastern foot of Helan Mountain DOI: 10.25165/j.ijabe.20221504.5406 Citation: Jiang T T, Yan P K, Ma T H, Wang R. Nutritional requirements and precise fertilization of wine grapes in the eastern foothills of Helan Mountain. Int J Agric & Biol Eng, 2022; 15(4): 147–153.